Development of CMR-derived aortic stiffness parameters in patients with metabolic comorbidities after ST-segment elevation myocardial infarction. (3rd October 2022) - Marjani, K; Erkens, R; Kramser, N; Ipek, R; Nienhaus, F; Haberkorn, W; Wischmann, P; Polzin, A; Roden, M; Jung, C; Kelm, M; Boenner, F; et al.
Abstract: Background: Aortic stiffness has demonstrated an independent prediction of adverse cardiovascular events after ST-segment elevation myocardial infarction (STEMI) [1]. The general impact of the comorbidities diabetes mellitus (DM), chronic kidney disease (CKD), anemia on aortic stiffness is well known [2, 3]. Therefore, the present study aimed to investigate the influence of metabolic comorbidities on cardiovascular magnetic resonance (CMR)-derived aortic parameters early and 6 months after STEMI. Methods: From the prospective STEMI pathway, 161 patients (mean age: 63.7 years; 75% male) with initial CMR 5 days after STEMI were included. 105 patients pursued in a 6-month follow-up CMR. Aortic stiffness was assessed using different parameters: 1) pulse wave velocity (PWV) from velocity-encoded phase-contrast images, 2) aortic distensibility, and 3) radial strain from the ascending aorta obtained from cine images. DM was diagnosed when either pre-existing, HbA1c ≥6.5% at index hospitalization or 2-hour OGCT ≥200 mg/dl. CKD was present when glomeruli filtration rate (GFR) was less than 60 ml/min/m 2, Anemia was defined according to WHO classifications. Results: Of the 161 patients, 46 presented with anemia at admission, 79 with anemia at day 5, 26 with CKD and 57 with DM. Initial anemia resulted in a significantly lower distensibility (p=0.003) and aortic strain (p=0.02). A correlation between initial haemoglobin levels and distensibility (r=0.253; p=0.002) was found. CKD Patients showed a lower distensibility (p=0.012). There were correlations between GFR and PWV (r=−0.298; p<0.001), distensibility (r=0.370; p<0.001), and radial strain (r=−0.388; p<0.001). After 6 month this significant correlation remained. The DM group showed higher PWV values (p=0.02) and a lower radial strain (p=0.003). PWV showed a correlation with the 2-hour OGCT value (r=0.249; p=0.011) while the radial strain correlated with HbA1c (r=0.216; p=0.007). After multivariable analyses, diabetes remained the only significant predictor to show higher PWV (p=0.004) and poorer radial strain values (p=0.0045) while initial anemia remained the only significant predictor of lower distensibility (p=0.0033). Aortic stiffness parameters did not show any changes after 6 months in all groups. Only NTproBNP 5 days after STEMI correlated significantly with 6-months PWV (r=0.247; p=0.02), radial strain (r=0.36; p=0.001), distensibility (r=−0.226; p=0.018). Conclusion: Anemia, DM and CKD show a detrimental impact on values of aortic stiffness early after STEMI. Diabetes remains the only significant predictor of higher PWV and poorer radial strain values after multivariable analysis while initial anemia remains significant predictor of lower distensibility. After 6 months none of the groups showed improvement in aortic stiffness parameters. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Sonderforschungsbereich 1116